Evaluating the impact of Pillars One and Two - Suranjali Tandon; Chetan Rao (South Centre, 2022)
The proposed OECD Pillar One and Two reforms mark a significant shift in the way large multinational enterprises are taxed on their global incomes. However, while considering the reform at the proposed scale tax administrators must be able to compare the revenue gains with alternatives. This paper uses open-source data to provide tentative estimates of the impact of Pillars One and Two. The methodology has been detailed so that administrators can replicate it for comparison. Further, the paper provides an assessment from the perspective of developing countries of some of the key design elements of the proposals so as to understand whether they are administrable and to foresee possible challenges.
Keywords: 300; Amount A; Automated Digital Services (ADS); Base Erosion and Profit Shifting Project (BEPS); Digital Service Taxes (DSTs); Double Taxation; Global Anti-Base Erosion (GloBE) Rules; Global Minimum Tax Rate; Global Tax; Global Taxation; Group of 20 (G-20); Group of Twenty-Four (G-24); Inclusive Framework; International Tax; International Tax Cooperation; International Taxation; Investment; Multilateral Instrument (MLI); Multinational Enterprises (MNEs); Organisation for Economic Co-operation and Development (OECD); Pillar One; Pillar Two; Tax; Tax Certainty; Tax Cooperation; Tax Dispute Resolution Mechanism; Tax Law; Tax Policy; Tax Reform; Taxation; Taxing Rights; The Multilateral Convention (MLC); Two Pillar Solution